Implementation of PhET simulation with discovery learning model to improve understanding of dynamic electricity concepts - Vera Meidy Anisa; Dyah Astriani (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study describes the implementation of learning using PhET simulation with a discovery learning model, the effect on increasing understanding of dynamic electricity concepts in science subjects, and student responses after participating in the lesson. This type of research uses a pre-experiment in the form of a one-group pretest-posttest design. The research was conducted on class IX IJHS students at Al-Islahiyah junior high school. Collecting data using the test method, questionnaire method, and observation method, with instruments in the form of test sheets, student response questionnaire sheets, and learning implementation observation sheets. The results of this study are 1) the implementation of learning using PhET simulation media with discovery learning model at first to fourth meetings is categorized as very good with percentages of 95.05%, 94.78%, 99.47%, and 100%. 2) The average n-gain value of all sub-concepts in class IX-A and class IX-B of 0.68 and 0.66, respectively, in the medium category indicate an increase in concept understanding. 3) The students show a positive response to the implementation of learning with PhET simulation with a discovery learning model with an average percentage of 74.28%. Thus, PhET simulation learning with a discovery learning model can improve students understanding of concepts.